Heavy Metals in the Imported and Iranian Rice Consumed in Hormozgan Province - Mohsen Dehghani; Fatemeh Mosaferi; Vali Alipour (Shiraz University of Medical Sciences, 2016)
Background: Given that the share of imported rice from India and Pakistan, the current study was conducted to determine the concentration of lead, arsenic and cadmium in the rice imported from the two mentioned countries in comparison to Iranian rice. Methods: This cross-sectional study was conducted in 2014 in Bandar Abbas, using a completely randomized block design. Five samples of each brand (India,Pakistan and Iran) and a total of 75 samples were selected. To measure the amount of arsenic in them, atomic spectrum poll and to determine the amount of lead and cadmium, the graphite furnace atomic absorption spectrometer optical-compliant were used. To analyze the data, we applied descriptive statistics and analysis of variance using SPSS software. Results: The mean of Cd, As and Pb were 0.045, 0.057, and 0.022 mg/kg, respectively. There was a significant difference for Cd in the local and imported rice (P=0.002). Difference for As in the local and imported rice was not significant (P=0.218). A statistically significant difference was found between the imported and Iranian rice (P=0.354). There were no significant differences among all the measured heavy metals in the tested samples of India and Pakistan rice, both legally and illegally (P=0.144). Conclusion: It was found that the rice was contaminated with heavy elements; it is recommended that measures should be taken to promote healthy rice production, including periodic monitoring of heavy metals in the water and rice seeds, establishing an appropriate operating system to reduce heavy metal emissions, using international experiences on the effects and complications of heavy metals in water resources and farming, and performing quality control measures on the imported rice